2022
DOI: 10.3390/buildings12081205
|View full text |Cite
|
Sign up to set email alerts
|

Green Building Construction: A Systematic Review of BIM Utilization

Abstract: As a multi-function method, Building Information Modeling (BIM) can assist construction organizations in improving their project’s quality, optimize collaboration efficiency, and reduce construction periods and expenditure. Given the distinguished contributions of BIM utilization, there is a trend that BIM has significant potential to be utilized in the construction phase of green buildings. Compared with traditional buildings, green buildings have more stringent requirements, including environmental protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 177 publications
(440 reference statements)
0
10
0
Order By: Relevance
“…Cao Yu et al studied the application of BIM technology in the construction process of green buildings and found that BIM technology is used in green building construction. It plays a big role in quality improvement, data storage, and collaborative optimization [43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cao Yu et al studied the application of BIM technology in the construction process of green buildings and found that BIM technology is used in green building construction. It plays a big role in quality improvement, data storage, and collaborative optimization [43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, BIM also can simulate (Ansah et al, 2019;Farahaneza et al, 2018;Gao et al, 2019;Memon et al, 2014;Wen et al, 2020) energy efficient analysis (Ghaffarianhoseini et al, 2016;Mirpanahi & Noorzai, 2021;Raouf & Al-Ghamdi, 2018) which in line with the goal of green building projects where to minimize the uses of energy of the building. BIM has been proven as a very beneficial approach in reducing uncertainties and improving the efficiency of the construction process (Cao et al, 2022;Eadie et al, 2013;Memon et al, 2014;Pu & Wang, 2021;Sacks et al, 2018), increasing the speed and utility of activities and improving the interaction between stakeholders (Huang et al, 2020b).…”
Section: Building Information Modellingmentioning
confidence: 99%
“…A green building is a high-quality building that can conserve resources, protect the environment, minimize pollution, and provide occupants with a healthy, suitable, and efficient living environment, maximizing the benign coexistence of human beings and nature during the entire lifecycle of green buildings [9][10][11]50,67,[69][70][71][72][73][74]76,78,82,83,85,87]. The earliest official concepts of the modern green building date back to the 1960s [53][54][55].…”
Section: An Overview Of Green Building Development In Chinamentioning
confidence: 99%
“…According to the Evaluation Standard of Green Building in China, green buildings are buildings that provide environmental benignity, energy savings, pollution reduction, healthy residential environments, and comfortable utilization experiences throughout the entire lifecycle of the asset [9]. Compared to conventional architecture, green buildings have some significant advantages and benefits, including a low negative environmental impact, no toxic gas emissions, a preference for recycled materials and renewable energy utilization, and high residential satisfaction [10,11]. Based on the abovementioned contributions, green buildings have significant advantages regarding environmental protection and public health optimization.…”
Section: Introductionmentioning
confidence: 99%